2009
DOI: 10.1002/cne.22127
|View full text |Cite
|
Sign up to set email alerts
|

Retinal ganglion cells in the eastern newt Notophthalmus viridescens: Topography, morphology, and diversity

Abstract: The topography and morphology of retinal ganglion cells (RGCs) in the eastern newt were studied. Cells were retrogradely labeled with tetramethylrhodamine-conjugated dextran amines or horseradish peroxidase and examined in retinal wholemounts. Their total number was 18,025 +/- 3,602 (mean +/- SEM). The spatial density of RGCs varied from 2,100 cells/mm(2) in the retinal periphery to 4,500 cells/mm(2) in the dorsotemporal retina. No prominent retinal specializations were found. The spatial resolution estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…All three types are arranged as regular mosaics spatially independent from each other, providing strong evidence for their being natural GC types (Cook et al, ; Cook, ). Cell types similar to α a , α c , and biplexiform cells are also found in nonmammalian species (e.g., Cook and Noden, ; Pushchin and Karetin, ). Their presence in the Steller's sculpin supports the hypothesis of the symplesiomorphy and potential homology of large GCs in nonmammals (Cook et al, ).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…All three types are arranged as regular mosaics spatially independent from each other, providing strong evidence for their being natural GC types (Cook et al, ; Cook, ). Cell types similar to α a , α c , and biplexiform cells are also found in nonmammalian species (e.g., Cook and Noden, ; Pushchin and Karetin, ). Their presence in the Steller's sculpin supports the hypothesis of the symplesiomorphy and potential homology of large GCs in nonmammals (Cook et al, ).…”
Section: Discussionsupporting
confidence: 73%
“…Our previous research showed that parameters related to soma size proved to be least discriminating ones, and their inclusion into analysis often had masking effects, deteriorating the clustering quality (Pushchin and Karetin, ). For these reasons, these parameters were not used in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of morphological characteristics (Rodieck and Brening, 1983;Cook, 1998) can be used to provide an indication of the retinal ganglion cell types present. Recent methods using an "unsupervised" quantitative approach, such as cluster analysis, have become increasingly popular for objectively segregating cells into types (Costa and Velte, 1999;Badea and Nathans, 2004;Kong et al, 2005;Coombs et al, 2006Coombs et al, , 2007Pushchin and Karetin, 2009). These methods, combined with improved technology for digital reconstruction, provide greater objectivity and validity to morphological classification of neurons than previous methods.…”
Section: Indexing Terms: Vision; Retina; Morphology; Evolution; Simprmentioning
confidence: 99%
“…Multimodality is important for variables used in cluster analysis. If a variable is unimodally distributed, then it is less likely to be helpful for cluster analysis (Schweitzer and Renehan, 1997;Pushchin and Karetin, 2009). The parameter with the largest MI from each category of parameters was chosen.…”
Section: Parameter Selectionmentioning
confidence: 99%
“…Parameters with the lowest MIs and least discriminating power, as revealed by discriminant function analysis, were successively excluded from the clustering models as previously described (Pushchin and Karetin, 2009). We also used the automatic variable weighting (OVW) algorithm to improve the clustering quality (De Soete, 1986Soete, , 1998Makarenkov and Legendre, 2001).…”
Section: Classificationmentioning
confidence: 99%